A Biomass‐Derived Non‐Noble Cobalt Catalyst for Selective Hydrodehalogenation of Alkyl and (Hetero)Aryl Halides. (30th June 2017) - Sahoo, Basudev; Surkus, Annette‐Enrica; Pohl, Marga‐Martina; Radnik, Jörg; Schneider, Matthias; Bachmann, Stephan; Scalone, Michelangelo; Junge, Kathrin; Beller, Matthias
Abstract: Hydrodehalogenation is a straightforward approach for detoxifications of harmful anthropogenic organohalide‐based pollutants, as well as removal of halide protecting groups used in multistep syntheses. A novel sustainable catalytic material was prepared from biowaste (chitosan) in combination with an earth‐abundant cobalt salt. The heterogeneous catalyst was fully characterized by transmission electron microscope, X‐ray diffraction, and X‐ray photoelectron spectroscopy measurements, and successfully applied to hydrodehalogenation of alkyl and (hetero)aryl halides with broad scope (>40 examples) and excellent chemoselectivity using molecular hydrogen as a reductant. The general usefulness of this method is demonstrated by successful detoxification of non‐degradable pesticides and fire retardants. Moreover, the potential of the catalyst as a deprotection tool is demonstrated in a multistep synthesis of (±)‐peronatin B (alkaloid).